An integrated threat theory analysis of latent tension between native Indonesians and Chinese Indonesians - Yotes TS; Croucher SM (Taylor and Francis Group on behalf of the National Communication Association, 2024)
The relationship between Chinese Indonesians and native Indonesians (Pribumi) is marred by tensions and violence. The Dutch colonial legacies have positioned Chinese Indonesians as perpetual outsiders, making them constantly question their roles and identity in the process of Indonesian nation-building. Despite their centuries-old presence and Indonesia’s almost three decades of reform, prejudice towards Chinese Indonesians persists. This was reflected in the 2017 Indonesia National Survey Project, suggesting native Indonesians still perceive their Chinese Indonesian counterparts as an economically privileged group, greedy, selfish, and exclusive. Using integrated threat theory, this study explores the link between the perception of threats and prejudice towards Chinese Indonesians. Using multiple regression analysis, this study found stereotypes, realistic threats, history of intergroup conflicts, and age are strong predictors of prejudice towards the ethnic Chinese in Indonesia. Theoretical, methodological, and practical implications for integrated threat and prejudice are discussed.
Keywords: Integrated threat; prejudice; stereotypes; Chinese Indonesian; intergroup communication